Notocrater christofferseni n. sp. (Vetigastropoda: Pseudococculinidae): first record of the genus in the South Atlantic Ocean - Lima, Silvio Felipe Barbosa (Zootaxa, 2014)
This paper reports the genus Notocrater Finlay, 1926 from the South Atlantic Ocean based on the description of a new species, Notocrater christofferseni n. sp. from deep waters off northeastern Brazil. Notocrater christofferseni n. sp. is compared with N. houbricki McLean & Harasewych, 1995 and N. youngi McLean & Harasewych, 1995. The new species differs from these congeners mainly by the anterior region, which comprises about 95% of shell length and has double pustule rows (about 50) arranged concentrically from the anterior margin to the center of the shell. The present study extends knowledge of the latitudinal and bathymetric distribution of Notocrater from the Bahamas (26°N; 518 m) to the Southeastern Atlantic (northeastern Brazil: 10°S; 720 m).